'An essential right': reflections on evaluating a professional development program for tutors. Issue 1 (2nd January 2017) - Fredericks, Vanessa; Bosanquet, Agnes
Abstract: While there is a growing body of research on sessional staff experiences, there are few published accounts evaluating their professional development. This paper reflects on an evaluation of a university-wide professional development program for tutors at an Australian university. A combination of complementary approaches were used to inform the development of the evaluation, namely: Participatory Action Research, monitoring, evaluation, research and improvement, and Participatory Evaluation. Findings of the evaluation reveal valuable lessons for the academic development of sessional teaching staff.